5x - 8a + 4a - 2x + a = 3x - 3a
3a * * * * * Actually, it is 4a.
4a+5=25 4a=25-5 4a=20 a=20/4 a=5
3a - 2b
Add them together: 3a+4a-a = 6a
It is -44 + 4a
6a - 8 - 4a - 2 → 6a - 4a - 8 - 2 → 2a - 10
The answer to 4a times 3b equals 1.3. You have to find the value of A and B.
48a3 + 32a2 + 4a = 4a(12a2 + 8a + 1)
Without any signs between what appear to be terms, it is not possible to simplify.
a2 - 4a + 4
21a - 6a
You need to combine the different parts that contain the variable "a". Just add the coefficients together algebraically.
5ab-2ab+4a-b+5b = 3ab+4a+4b
If the question was 3a + 4a - a, the answer is 6a. If the question was something else please resubmit using words eg "plus", "divide", "equals" because the browser used for posting questions does not like symbols!
10a + 3a - 4a = 9a
is that ment to be a > sign? well if it is3a>4a-5 (-4a)-a>-5 then just inverta>5
It is an expression of two terms as: 4a+12
"a" plus "3a" is equal to 4a. (3a+a=4a). You already have 3 "a's" and then you add another "a."